Exogenous Silicon Attenuates Cadmium-Induced Oxidative Stress in Brassica napus L. by Modulating AsA-GSH Pathway and Glyoxalase System - Hasanuzzaman, Mirza; Nahar, Kamrun; Anee, Taufika Islam; Fujita, Masayuki (Frontiers in Plant Science, 2017)
Cadmium (Cd) brings a devastating health hazard to human being as a serious consequence of agricultural and environmental contamination. We demonstrated the protective effect of silicon (Si) on cadmium (Cd)-stressed rapeseed (Brassica napus L. cv. BINA Sharisha 3) plants through regulation of antioxidant defense and glyoxalase systems. Twelve-d-old seedlings were exposed to Cd stress (0.5 and 1.0 mM CdCl2) separately and in combination with Si (SiO2, 1.0 mM) for two days. Cadmium toxicity was evident by an obvious oxidative stress through sharp increases in H2O2 content and lipid peroxidation (malondialdehyde, MDA content), and visible sign of superoxide and H2O2. Cadmium stress also decreased the content of ascorbate (AsA) and glutathione (GSH) as well as their redox pool. The activities of monodehydroascorbate reductase (MDHAR), dehydroascorbate reductase (DHAR) and catalase (CAT) were decreased by Cd while ascorbate peroxidase (APX) and glutathione S-transferase (GST) activities were increased. The enzymes of glyoxalase system (glyoxalase I, Gly I and glyoxalase II, Gly II) were also inefficient under Cd stress. However, exogenous application of Si in Cd treated seedlings reduced H2O2 and MDA contents and improved antioxidant defense mechanism through increasing the AsA and GSH pools and activities of AsA-GSH cycle (APX, MDHAR, DHAR and GR) and glyoxalase system (Gly I and Gly II) enzymes and CAT. Thus Si reduced oxidative damage in plants to make more tolerant under Cd stress through augmentation of different antioxidant components and methylglyoxal detoxification system.